2009
DOI: 10.1007/s00246-009-9427-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Surgery in Patients with Trisomy 18

Abstract: Cardiac surgery is infrequently but increasingly being used to repair congenital heart defects associated with trisomy 18. The clinical details of trisomy 18 patients undergoing cardiac surgery have rarely been reported. Seventeen patients with trisomy 18 and serious cardiac symptoms underwent cardiac surgery in our institution. Age at surgery ranged from 7 to 258 days (median, 66 days). One patient had an atrioventricular septal defect and coarctation of the aorta. The remaining patients had ventricular septa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 21 publications
6
75
1
1
Order By: Relevance
“…A review of 17 patients with ES in which either palliative surgery or primary intracardiac repair was completed reported that only one patient died due to heart failure. These results suggest that the use of cardiac surgery may be correlated with a reduction in heart failure-related deaths in ES patients [6]. Another recent review of the Pediatric Cardiac Care Consortium registry reported that of 35 total patients (11 with PS and 24 with ES) who underwent surgical repair of CHD, 91 % survived to hospital discharge [3], further supporting the notion that PS and ES patients can survive cardiac surgery.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A review of 17 patients with ES in which either palliative surgery or primary intracardiac repair was completed reported that only one patient died due to heart failure. These results suggest that the use of cardiac surgery may be correlated with a reduction in heart failure-related deaths in ES patients [6]. Another recent review of the Pediatric Cardiac Care Consortium registry reported that of 35 total patients (11 with PS and 24 with ES) who underwent surgical repair of CHD, 91 % survived to hospital discharge [3], further supporting the notion that PS and ES patients can survive cardiac surgery.…”
Section: Discussionmentioning
confidence: 88%
“…Although cardiac surgery has been applied infrequently in the past for PS and ES, the current literature demonstrates that it is now being increasingly employed as a management strategy for ES patients with CHD [6]. In addition, as the surgical strategies used for correction of CHD are not always curative, other interventions or additional surgeries are also not uncommon.…”
Section: Discussionmentioning
confidence: 97%
“…3,5,18,[23][24][25][26][27][28] The risks of PDA, RDS, and BPD were increased among infants with T13 or T18 compared with infants without birth defects. Our study and the majority of other studies cited here provide little information on the quality of life experienced by the surviving infants with T13 or T18.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Japan suggest growing willingness to perform surgical interventions for the cardiac anomalies most common in trisomy 18, including ventriculoseptal and atrioseptal defects and patent ductus arteriosus. 9,10 An estimated 60% to 80% of fetuses with trisomy 18 have congenital heart disease; one-third of these have complex lesions. 11 Experience with cardiac repairs for infants with trisomy 18 or 13 is limited.…”
Section: The Fetal Medicine Team's Responsementioning
confidence: 99%